Utilization of Used Cooking Oil from Street Vendor: Recycle and Anti-Oxidant Enrichment with Moringa oleifera leaves - Ismet, Rhahmasari; Sianipar, Rut Novalia Rahmawati; Adelia, Nesha; Filaila, Euis; Jovianto, Andrian; Firdaus, Ridwan; Hanifah, Hanifah; Dwiastuti, Rahma; Aninda, Yunita; Alfiona, Della; Akmalina, Rifkah; Iswantini, Dyah; prasetyo, Joni (Molekul, 2024)
Used cooking oil (UCO) is abundant in Indonesia because of lifestyle of people. Especially UCO from street vendors had very low quality based on its Free Fatty Acid (FFA) content that reached 5.074%. When UCO was deposed into drainage, it would pollute the environment. Low grade UCO from street vendors contained Unsaturated-Fatty-Acid, Saturated-Fatty-Acid, and other hydrocarbons. Recycling UCO to replace edible oil considered more desirable rather than biodiesel since higher added value. FFA was the most undesired compound affecting cooking oil quality. FFA reducing with diluted 0.1 M NaOH 10% v/v could reduce FFA from 5.07% to 0.53%. Bleaching earth (BE) content mostly Si, Nb, Al, Ca and Na was safe to treat UCO for edible cooking oil. BE played cleaning UCO but absorbed the oil 17%. ANOVA analysis for BE and Moringa oleifera leaves (MOL) treatment fits with Reduced Quadratic model. Based on the ANOVA, the model showed that the decrease of FFA was determined significantly by BE amount and temperature with P-values less than 0.05. Optimization for BE treatment was done using Response Surface Method to find out the lowest FFA. And based on the simulation, it was obtained 0.2854% while the experimental results showed 0.2908%. Furthermore, BE combined with Moringa oleifera leaves (MOL) that known anti-oxidant source was used to treat UCO. UCO originally content stronger anti-oxidant activity rather fresh palm oil with IC50 62.12 and 83.03 mg/kg, respectively. Stronger anti-oxidant in UCO allegedly derived from fried foods. Treatment 10% BE and 5% MOL considered optimal for good appearance edible oil, little yellow greenish. Moreover, GC/MS analysis showed improvement active compounds in treated UCO with 5, 7.5 and 10 g MOL in 150 ml UCO with 24.36%, 30.32% and 37.76% active compounds, respectively. Moreover, anti-oxidant measured with IC50 the treated UCO were 43.18, 42.33 and 41.78 mg/kg, respectively. Increasing the number of MOL did not significantly increase the anti-oxidant activity. Anti-oxidant detected in treated UCO identified such as ethyl acridine, indolizine derivatives, cyclotrisiloxane-hexamethyl, benzimidazoles, and Fumaric acid. Based on the results, UCO recycling is applicable for a community, save expenses and strengthen food security and food sovereign. Further thought for its implementation is to design an integrated system from collecting UCO in a reservoir tank equipped with filter, recycling process and finally product tank at mini plant scale. Keywords: Anti-oxidant enrichment, bleaching earth, edible treated UCO, Moringa oleifera leaves (MOL) , UCO recycle